Forest Resource Information on the Internet: Connecting to Today’s Online Resources - Chris Demers (EDIS, 2014)
In 1997, the UF/IFAS School of Forest Resources and Conservation (SFRC) published Forest Resource Information on the Internet, which provided detailed information about the Internet: its history, structure, and how to use it. It also provided a sample of forest resource websites. Much has changed since the first publication. This is the third revision of this document, providing updated information on the latest landowner assistance websites available. These state, regional, and national resources can serve as a springboard to a wide variety of natural resource information and programs. This 4-page fact sheet was written by Chris Demers and published by the UF Department of School of Forest Resources and Conservation, May 2014.